Viewpoint - Simon, Judit (2023)
One in eight individuals worldwide lives with a mental health disorder. For many European countries, the prevalence is even higher, with one in four people reporting mental health problems [1]. Three-quarters of all mental health disorders develop before age 25, with many presenting initially in undiagnosed forms already in the mid-teens and eventually manifesting as severe disorders and lasting into old age [2]. There is also growing evidence that mental health disorder symptoms cross diagnoses and people frequently have more than one mental health disorder [3].